In vivo Characterization of Amorphous Silicon Carbide As a Biomaterial for Chronic Neural Interfaces - Knaack, Gretchen L.; McHail, Daniel G.; Borda, German; Koo, Beomseo; Peixoto, Nathalia; Cogan, Stuart F.; Dumas, Theodore C.; Pancrazio, Joseph J. (Frontiers in Neuroscience, 2016)
Implantable microelectrode arrays (MEAs) offer clinical promise for prosthetic devices by enabling restoration of communication and control of artificial limbs. While proof-of-concept recordings from MEAs have been promising, work in animal models demonstrates that the obtained signals degrade over time. Both material robustness and tissue response are acknowledged to have a role in device lifetime. Amorphous Silicon carbide (a-SiC), a robust material that is corrosion resistant, has emerged as an alternative encapsulation layer for implantable devices. We systematically examined the impact of a-SiC coating on Si probes by immunohistochemical characterization of key markers implicated in tissue-device response. After implantation, we performed device capture immunohistochemical labeling of neurons, astrocytes, and activated microglia/macrophages after four and eight weeks of implantation. Neuron loss and microglia activation were similar between Si and a-SiC coated probes, while tissue implanted with a-SiC displayed a reduction in astrocytes adjacent to the probe. These results suggest that a-SiC has a similar biocompatibility profile as Si, and may be suitable for implantable MEA applications as a hermetic coating to prevent material degradation.